Business Retention and Expansion (BRE) Programs: Why Existing Businesses Are Important - Henry M. Cothran (EDIS, 2006)
FE-651, a 2-page fact sheet by Henry M. Cothran, is the first in a series of ten on establishing Business Retention and Expansion programs. This fact sheets summarizes the results from several studies over the last decade showing how existing businesses are responsible for more job growth in local communities than industry attraction efforts and lists several other benefits existing businesses provide to communities. Includes references. Published by the UF Department of Food and Resource Economics, September 2006.